A Study On The Applications Of Geospatial Engineering Techniques In Mineral Mapping And Geotoxicological Risk Assessment Of Mining Land Contamination In Ulu Johan, Kinta Valley Tinfield - Abu-Libda, Osama Ahmad Mustafa (2008)

(untitled)
Pemineralan semulajadi dan kegiatan perlombongan yang berterusan telah menghasilkan banyak bahan pemala yang berpotensi memberi kesan terhadap persekitaran yang mungkin boleh menyebabkan pencemaran tanah dan risiko kepada kesihatan manusia dan ekosistem. Pencirian geoenviromen dan penilaian pemalaan tanah (seperti yang dirancang dalam Penilaian Tapak Enviromen Fasa I dan II> telah dilakukan dalam kajian ini dengan menggabungkan teknik terkini perlombongan dan kejuruteraan georuang. Kajian awal menunjukkan kualiti tanah yang kurang memuaskan disebabkan gangguan secara semulajadi dan kegiatan manusia. Dalam tasa kajian risiko, prosedur geokimia carigali telah dilakukan dengan mengambil 25 sampel tanah, GPS dirujuk, pada kedalaman kurang daripada 40 sm secara rambang. Kepekatan unsur As, Zn, Mn, Pb, Te, Sb dan Zr di dalam sampel (saiz 10 mesh) telah dianalisis menggunakan ICP-OES. Natural mineralization and intermittent mining operations in Ulu Johan, Kinta Valley tinfield have resulted in generating enormous quantities of contaminants of potential hazard in the environment, thereby contaminating the land asset and imposing significant risk to human health and ecosystem. A geoenvironmental characterization and assessment of soil contamination planned in Environmental Site Assessment Phase I and Phase II, had been carried out in this study by the integration of state-of-the-art techniques of mining geoscience and geospatial engineering. The preliminary risk assessment phase revealed deterioration of land quality due to natural and anthropogenic disturbances of regolith materials. In the quantitative risk assessment phase, a geochemical exploration procedure was undertaken to collect, prepare and analyze a total of 25 GPSgeoreferenced soil samples extracted at average depth <40 cm by random sampling. The 10-mesh-sized samples were analyzed by ICP-OES for elements As, Zn, Mn, Pb, TI, Sb and Zr then mapped-out using geostatistical spatial interpolation modeling by kriging and geovisulaized thematically in GIS.